ANALISIS PENGARUH LOKASI, WORD OF MOUTH, DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA WIRVET PETSHOP SITUBONDO - Novia Susanti; Triska Dewi Pramitasari; Muhammad Iqbal Anshory (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
The increasing trend of keeping pets drives the growth of the pet shop industry, along with public awareness of the importance of animal care. Pet shop marketing management is required to understand customer needs, build trust, utilize digital marketing, and choose strategic locations to create loyalty and competitiveness in an ever-growing market. The purpose of this study was to analyze the Influence of Location, Word of Mouth, and Service Quality on Customer Loyalty, through Customer Satisfaction as an Intervening Variable at Wirvet pet shop in Situbondo. The sampling technique was determined by simple random sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application showed that Location has a positive and significant effect on customer satisfaction. Word of mouth has a positive and significant effect on customer satisfaction. Service quality has a positive but insignificant effect on customer satisfaction. Location has a positive and significant effect on customer loyalty. Word of mouth has a positive but insignificant effect on customer loyalty. Service quality has a positive but insignificant effect on customer loyalty. Customer satisfaction has a positive but insignificant effect on customer loyalty. Location has a positive but insignificant effect on customer loyalty through customer satisfaction. Word of mouth has a positive but insignificant effect on customer loyalty through customer satisfaction. Service quality has a positive but insignificant effect on customer loyalty through customer satisfaction.